Information exchange in laboratory markets: competition, transfer costs, and the emergence of reputation - Roman Hoffmann; Bernhard Kittel; Mattias Larsen (Experimental Economics, 2020)
Public reputation mechanisms are an effective means to limit opportunistic behavior in markets suffering from moral hazard problems. While previous research was mostly concerned with the influence of exogenous feedback mechanisms, this study considers the endogenous emergence of reputation through deliberate information sharing among actors and the role of barriers in hindering information exchange. Using a repeated investment game, we analyze the effects of competition and transfer costs on players' willingness to share information with each other. While transfer costs are a direct cost of the information exchange, competition costs represent an indirect cost that arises when the transfer of valuable information to competitors comes at the loss of a competitive advantage. We show that barriers to information exchange not only affect the behavior of the senders of information, but also affect the ones about whom the information is shared. While the possibility of sharing information about others significantly improves trust and market efficiency, both competition and direct transfer costs diminish the positive effect by substantially reducing the level of information exchange. Players about whom the information is shared anticipate and react to the changes in the costs by behaving more or less cooperatively. For reputation building, an environment is needed that fosters the sharing of information. Reciprocity is key to understanding information exchange. Even when it is costly, information sharing is used as a way to sanction others.
Keywords: C9; D6; D8; G1; L1; 330; Reputation; Trust; Moral hazard; Information sharing; Competition; Experiment